Assessing the Risk of QT Prolongation in a Psychiatric Inpatient Cohort: A Retrospective Cross-Sectional Study - Johan Frederik Mebus Meyer Christensen; Jonathan Hugo Jürgens-Lahnstein; Afrim Iljazi; Stig Ejdrup Andersen; Morten Dahl; Gesche Jürgens (MDPI AG, 2024)
Background: QT prolongation is a potential serious adverse drug reaction, and assessing the risk of QT-prolonging drugs is routinely included in psychotropic medication reviews. However, the actual clinical benefits of such assessments are unknown. We investigate whether QT prolongation (QTc value > 480 ms) manifests in psychiatric inpatients at risk of QT prolongation as identified by assessing drug regimens. Secondly, we test the predictive value of well-known risk factors for QT prolongation. Results: The median patient age was 49 years (IQR 34-64) for patients treated with a median of nine drugs (IQR 6-12) and a median QT-prolonging drug sum of three daily defined dosages (IQR 1.88-4.76). We extracted 290 ECGs for patients where pharmacist-led-medication reviews (PMRs) identified an increased risk of QT prolongation and 190 ECGs for patients with no such risk, identifying 33 cases of verified QT prolongation equally distributed between groups. Unadjusted regression analysis revealed that advanced age (OR 3.27 CI 95% 1.60-6.84) and cardiovascular comorbidity (OR 3.53 CI 95% 1.71-7.29) were associated with manifest QT prolongation, while the QT-prolonging drug load was not. Methods: We reviewed electronic health records (EHRs) of 799 psychiatric inpatients exposed to PMRs made from 1 September 2016 to 31 December 2018 in Region Zealand Denmark. Conclusions: Patients at risk of QT prolongation as identified by drug reviews rarely manifests with actual QT prolongation. Non-pharmacological risk factors seem to be better predictors for identifying patients with QT prolongation.